SWOT analysis as HR development and performance assessment PT. Santosa Kurnia Jaya - Nurfitasari, Anggiani; Sumadhinata, Yelli Eka (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research was conducted at PT. Santosa Kurnia Jaya to determine the company's business strategy by analyzing the company's strengths, weaknesses, opportunities, and threats. The type of approach taken is to use qualitative methods through SWOT analysis, then analyzed using IFAS and EFAS matrices to get the right business strategy for PT. Santosa Kurnia Jaya. Based on the results of the SWOT analysis in this company improving human resource development and employee performance is good, because refers to the results of the IFAS and EFAS matrices, from the internal factor analysis (IFAS), namely, the company shows that the quality of production results has a major effect on the survival of the company. The results of the IFAS table, found that the high market demand and company image greatly affect the company. At this time the company is in the business development phase because its in the I SO quadrant position (2.572; 2.277). PT. Santosa Kurnia Jaya is also trying to maintain the development of human resources following the company. For employee performance and tries to improve the performance of its employees to achieve the goals following the company's expectations. The right strategy that must be used is the Strength-Opportunities strategy.